A script in reverse: a didactical proposal for a reading of Lucrécia D’A Ferrara - Martino, Luis Mauro Sa (Comunicação & Educação, 2022)
How to read Lucrecia Ferrara’s work? Certainly there is more than one way to deal with an intellectual production that deals with several subjects, from communication theory to urbanism, from design to semiotics and beyond. This paper intends to provide a draft for a reading of her work by presenting some of her main books, mainly in chronological order. It emerges from the classroom need for an initial presentation of Ferrara’s work, directed to undergraduate students or someone in the first steps of graduate studies. It does not intend to be a complete or critical discussion of her ideas, but only an aid for future readers. Grounded on bibliographical research, this paper briefly places her books in the context of communication studies.